Beyond the Hofmeister Series: Ion-Specific Effects on Proteins and Their Biological Functions - Okur, Halil I; Hladílková, Jana; Rembert, Kelvin B; Cho, Younhee; Heyda, Jan; Dzubiella, Joachim; Cremer, Paul S; Jungwirth, Pavel (The journal of physical chemistry. B, 2017)
Ions differ in their ability to salt out proteins from solution as expressed in the lyotropic or Hofmeister series of cations and anions. Since its first formulation in 1888, this series has been invoked in a plethora of effects, going beyond the original salting out/salting in idea to include enzyme activities and the crystallization of proteins, as well as to processes not involving proteins like ion exchange, the surface tension of electrolytes, or bubble coalescence. Although it has been clear that the Hofmeister series is intimately connected to ion hydration in homogeneous and heterogeneous environments and to ion pairing, its molecular origin has not been fully understood. This situation could have been summarized as follows: Many chemists used the Hofmeister series as a mantra to put a label on ion-specific behavior in various environments, rather than to reach a molecular level understanding and, consequently, an ability to predict a particular effect of a given salt ion on proteins in solutions. In this Feature Article we show that the cationic and anionic Hofmeister series can now be rationalized primarily in terms of specific interactions of salt ions with the backbone and charged side chain groups at the protein surface in solution. At the same time, we demonstrate the limitations of separating Hofmeister effects into independent cationic and anionic contributions due to the electroneutrality condition, as well as specific ion pairing, leading to interactions of ions of opposite polarity. Finally, we outline the route beyond Hofmeister chemistry in the direction of understanding specific roles of ions in various biological functionalities, where generic Hofmeister-type interactions can be complemented or even overruled by particular steric arrangements in various ion binding sites.
Keywords: Proteins; proteiny; Molecular Dynamics Simulation; simulace molekulární dynamiky